Modelo Prolab: Play Again, servicio innovador que aborda la rotación constante de juguetes, que a menudo resulta en altos niveles de desperdicio - Aguilar Díaz, Fiorella Martin (2024)
The Play Again project addresses the problem of high toy turnover, which results in high levels of waste, negatively impacting the environment. This problem is especially relevant in zones 6 and 7 of Metropolitan Lima, where consumerism and waste generation by the toy industry have a significant negative environmental impact. The design of the solution involved the creation of an innovative toy rental service. This service was conceptualized to reduce toy waste and encourage sustainable consumption practices among SES B families with children between 2 and 12 years old. Experiments, surveys and usability tests were developed to validate the value proposition and ensure its acceptance in the market. The solution also aligned with Sustainable Development Goal (SDG) 12, Responsible Production and Consumption: By encouraging renting instead of buying, the production of new toys and associated waste is reduced. The business model has been financially evaluated, reaching a Net Present Value (NPV) of S/622,279 and a Modified Internal Rate of Return (MIRR) of 29.14%, which indicates its viability and profitability. Furthermore, from a social perspective, a social NPV has been calculated that reflects the positive impact of the project on the community and the environment, contributing to the conservation of resources and the reduction of waste.